Anaesthesia For Caesarean Section of Single Umbilical Artery and Herpes Simplex Virus Type 1 Ig M Positive Obstetric Patient (Annals of Medical Research, 2021)
None
Keywords: Obstetric Anaesthesia; Umbilical Cord Abnormality: Single Umbilical Artery, Herpes Simplex Virus Type 1 Infection.